(3efThQ aj PcQ EbGdI SYO ef LHd GdSeGbs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf cJHJ CWGd Gddg HbGA GNhGJi Ggd GdYGOI hGdUaG GdeJejRjf HGdGeGfg s
(3BNQgG (B:s
(3hjfSN dSYO HYO JbQjQg Yf O GdTjN CHj GdbGSe fUQ djMOK Gddg GdeGfI hGdTcQ JeJ hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis